SIMULASI PENGENDALIAN SUHU DI RUMAH TANAMAN JAMUR TROPIKA - Setiyo, Yohanes (Universitas Udayana, 2008)
A green house that roofed by using transparent materials such as glasses, fiberglass, plastic, etc. could provide an optimum growth environment for plants such as mushrooms. However, green house effect during the day leads to a higher temperature inside the green house in comparison to the outside temperature. In order to provide an optimal environment for growing mushrooms in a green house, it is required a temperature machine control which is able to bring the room temperatures between 160C to 210C. The dynamic of room temperature can be predicted by using a mathematical model simulation. A stimulation model developed by using Matlab program could be implemented in a temperature control machine in order to bring the room temperature between 160C, 190C and 210C. Research results showed that it took 16.8 minutes, 26.4 minutes, and 30 minutes to bring the room temperature down to 160C, 190C and 210C respectively. When the room temperature reaching the target temperature, the room temperature were varying within 0.010C.